RESPON PESERTA DIDIK TERHADAP PENGGUNAAN E-MODUL BERBASISI KEARIFAN LOKAL PADA MATERI GELOMBANG BUNYI - Mahesa, Riki Andre; Silitonga, Haratua Tiur; Hidayatullah, Muhammad Musa Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The problem currently faced is the rapid development of technology in this era, which is increasingly eroding culture and causing students to no longer prioritize morals in the learning process. To overcome this problem, an E-Module based on local wisdom was developed to understand the concept of sound waves. The method used is the RD (Research and Development) method with a modified ADDIE model, with a focus only on the implementation stage. In this article the discussion focuses on user responses in using this E-Module, the users in this case are class XII students at SMA Negeri 3 Sukadana who were given 10 assessment indicator questions. Based on a response test conducted on 20 students at SMA Negeri 3 Sukadana, an average response rate of 89.5% was obtained with very good criteria. Therefore, it can be concluded that developing an E-Module based on local wisdom is very suitable for use, according to student responses. Based on the results of the feasibility responses from students, it can be concluded that the E-Module developed can and is suitable for use in supporting learning in schools